THE SEMANTIC STRUCTURE OF COLOR TERMS IN UZBEK LANGUAGE (Web of Teachers: Inderscience Research, 2025)
This study explores the semantic structure of color terms in the Uzbek language, focusing on their categorization, cultural significance, and linguistic representation. By analyzing native Uzbek speakers' usage and perception of color terms, this research identifies the basic and derived color categories, their metaphorical extensions, and their role in cultural and linguistic contexts. The findings reveal that Uzbek color terms are deeply rooted in the cultural and natural environment, reflecting the unique worldview of Uzbek speakers. This study contributes to the broader field of linguistic typology and cognitive semantics by providing insights into the interplay between language, culture, and cognition.